“Understanding Consumer Perception of Green Supply Chain Practices in India: A Consumer Perspective Study” (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
As people become more aware of environmental issues and the importance of sustainability, their choices as consumers and the way businesses operate are changing. More and more companies are choosing to use green supply chain methods, like using eco-friendly packaging, sourcing materials in a sustainable way, and making their logistics more environmentally friendly. These actions help reduce their effect on the environment and also improve how they are seen by customers.This research looks at how Indian consumers view green supply chain practices. It is based on real data collected from people through a structured questionnaire that uses a five-point scale to measure their opinions. The study uses a descriptive approach, and tools like percentages and charts are used to understand the data better.The findings show that consumers are now more aware of environmental concerns and generally support companies that take sustainable steps. Factors like using eco-friendly packaging, being open and honest about their practices, and taking responsibility for the environment play a big role in what people choose to buy. However, one big challenge is that many people are still sensitive to price when it comes to buying greener products.In conclusion, green supply chain practices have a big effect on how consumers think and what they buy. The results can help businesses create better sustainability strategies and gain a stronger position in the market.